Peran Ekonomi Syariah dalam Mendukung Sustainable Development Goals (SDGs) - Laila Murningsih Novrian Wakhidah (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
Sustainable development is a global agenda that demands a development approach oriented not only toward economic growth but also toward social justice and environmental sustainability. The Sustainable Development Goals (SDGs) serve as a comprehensive development framework emphasizing a balance between economic, social, and environmental aspects. In this context, Islamic economics is viewed as an alternative economic system whose values ​​align with the principles of sustainable development. This study aims to analyze the role of Islamic economics in supporting the achievement of the SDGs. The research employed a qualitative approach using a literature review method, including national and international journals from 2021–2025 and official institutional reports. The study's findings indicate that Islamic economics contributes to the achievement of the SDGs through commercial Islamic finance and Islamic social finance. Instruments such as Islamic banking, zakat, and waqf play a role in poverty alleviation, inequality reduction, and increased financial inclusion. However, this contribution is still suboptimal due to limited literacy, product innovation, and policy synergy. This study concludes that strengthening the Islamic economic ecosystem has the potential to increase its contribution to sustainable development in Indonesia